Connecting Self-regulated Learning and Performance with Instruction Across High School Content Areas (Springer International Publishing, 2018)
This book shows how principles of self-regulated learning are being implemented in secondary classrooms. The 14 chapters are theoretically driven and supported by empirical research and address all common high school content areas. The book comprises 29 lesson plans in English language arts, natural and physical sciences, social studies, mathematics, foreign language, art, music, health, and physical education. Additionally, the chapters address students with special needs, technology, and homework. Each chapter begins with one or more lesson plans written by master teachers, followed by narratives explaining how the lesson plans were implemented. The chapters conclude with an analysis written by expert researchers of the self-regulated learning elements in the lessons. Each lesson and each analysis incorporate relevant educational standards for that area. Different types of high schools in several states serve as venues. This powerful new book edited by Maria K. DiBenedetto provides a unique and invaluable resource for both secondary teachers and researchers committed to supporting adolescents in the development of academic self-regulation. Each chapter is jointly written by teachers who provide a wealth of materials, including lesson plans, and researchers who situate these lesson plans and academic self-regulation goals within the larger work on self-regulation. The topics covered are far broader than any other book I have seen in terms of developing academic self-regulation, covering over a dozen content areas, including literacy, mathematics, social studies, the sciences, and the arts. Teachers and scholars alike will find this book a must read. Karen Harris, EdD, Arizona State University A practical and magnificent blend of educational research and application. This book goes beyond presenting the findings of research on self regulation by connecting detailed strategies that align with the standards to the research. DiBenedetto et al. clearly illustrate how to develop self regulated learners in the classroom. A refreshing must read for all secondary educators and educational researchers seeking to be well grounded in education research and practical application techniques. Heather Brookman, PhD, Fusion Academy- Park Avenue .